Selenium nanoparticles from Corchorus olitorius corrects polycystic ovarian syndrome by inhibition of hormonal imbalance, aromatase and cellular inflammation via hypothalamic-ovarian axis in female rat - T.E. Akintola; J.K. Akintunde; O.E. Eteng; F.C. Thomas; J.T. Adeleke (Endocrine and Metabolic Science)
Purpose: Women of fertile age are affected by an endocrine disorder called polycystic ovarian syndrome (PCOS) and is typified by polycystic ovaries, hyperandrogenism, and irregular menstruation. Because of their ability to pass through cellular barriers, nanodrugs have recently been recommended as a treatment for a number of disorders. Thus, the purpose of this study was to evaluate the efficacy of synthetized selenium nanoparticles from Corchorus olitorius leaves (CO-SeNPs) against hypertension coexisting with PCOS. Methods: There were nine groups consisting of Control, Letrozole, L-NAME, Letrozole + L-NAME, Letrozole + CO-SeNPs, L-NAME + CO-SeNPs, Letrozole + L-NAME + CO-SeNPs, Letrozole + metformin, CO-SeNPs only. Letrozole and L-NAME were used to induce hypertension and PCOS for 21 and 14 days, respectively. The estrus cycle was monitored and animals were sacrificed after 35 days. Result: The findings demonstrated that while letrozole and L-NAME decreased estrogen and progesterone levels, they significantly increased luteinizing hormone, follicle stimulating hormone, testosterone, aromatase, and 17β-hydroxysteroid dehydrogenase levels. Furthermore, in the hypothalamus, ovary, and uterine of rats with hypertensive PCOS, there was a substantial rise in tumor necrosis factor-α and monocyte chemoattractant protein-1, but a significant drop in Nrf-2. Conclusion: By lowering neuroendocrine hormones and steroidogenic enzymes, CO-SeNPs therapy reduced hypertension and PCOS.